The pain and pleasure of being what one is: Viewpoints of health professionals and patients about being overweight/obese - Vieira, Carla Maria; Turato, Egberto Ribeiro; Marques Oliveira, Maria Rita [UNESP]; Gracia-Arnaiz, Maria Isabel (Routledge Journals, Taylor & Francis Ltd, 2014)
The objective of this article is to discuss the meanings that health professionals and patients in treatment attribute to obesity. The research consisted of a qualitative survey in health, based on in-depth interviews with patients and professionals at an out-patient clinic at the University Hospital in Barcelona, Spain. Here, we discuss the concept of obesity, the meanings of diagnoses, the singularities involved in managing treatment, and the process of becoming ill, all in the light of the anthropology of health that has a sociocultural orientation. Obesity is usually seen by the professionals as a risk-factor disease. For patients, the incorporation of this rationality is procedural and is mixed in with other meanings attributed to being overweight/obese that have been gradually developed throughout life. A patient's autonomy in choosing to be fat, or obese, and to adhere to treatment, is defined as a process that requires support in order to come to joint proposals in caring for these problems.
Keywords: obesity; nutrition; culture; qualitative study; psychology